Combate contra el alga roja (Cephaleuros virescens kunze) en citricos - Almandoz, J.E.=700 1 Castellanos, L.; Perez, E.; Rivero, T.
(Es, En)
Ilus., 16 ref.
Keywords: CITRUS; FRUTALES; PLAGAS DE PLANTAS; CONTROL QUIMICO; EXPERIMENTACION EN CAMPO; CUBA; CEPHALEUROS VIRESCENS)